Obesity and steatosis promotes mitochondrial remodeling that enhances respiratory capacity in the liver of ob/ob mice. Issue 6 (28th February 2018) - Garcia, Jerome; Decker, Carl W.; Sanchez, Silvestre J.; Ouk, Jeffrey M.; Siu, Krysta M.; Han, Derick
Abstract : We investigated if obesity/steatosis promotes mitochondrial remodeling in the liver of ob/ob mice (an obesity model). Liver mitochondria from ob/ob mice (21 weeks with significant steatosis) had 2‐fold increases in state III respiration compared with control (C57BL/6J, C57BL/6NJ) for all respiratory substrates examined (glutamate/malate, succinate, octanoate, and glycerol 3‐phosphate). A corresponding 2‐fold increase in the expression of respiratory complexes (I, IV, and V) and other respiratory proteins (glycerol phosphate dehydrogenase‐2 and medium‐chain acyl‐coenzyme A dehydrogenase) occur in liver mitochondria of mature ob/ob mice. Conversely, respiration in liver mitochondria from young ob/ob mice (6 weeks) does not differ from control with any respiratory substrates examined. Overall, mitochondrial remodeling that enhances respiration increases with obesity/steatosis in the liver of ob/ob mice. Abstract :